Homonymous Quadrantanopia as the First Manifestation of Cerebral Infarction: A Case Report: Poster Presentation - Case Report - Resident - dr. Rizki Dwayana Putra; Muhammad Hidayat (Ophthalmologica Indonesiana, 2024)
Abstract Introduction : Homonymous quadrantanopia, a visual impairment caused by lesions in the occipital lobe is typically due to vascular or traumatic injuries with tumors, abscesses, demyelination, or toxic substances in the white matter in rarer cases. Cerebral infarction in the occipital lobe is often diagnosed by ophthalmologists since initial symptoms involve visual disturbances without neurological symptoms. Case Illustration : A 52-year-old woman complained visual disturbance in the upper left visual field. Ophthalmologic examination showed normal visual acuity (6/6), pupillary response, and fundus appearance. The patient had history of hypertension for the past three years. Laboratory findings revealed hypercholesterolemia (240 mg/dl) and increased fasting blood sugar levels (102 mg/dl). A Brain CT scan identified infarction in the right occipital lobe and perimetry revealed left superior homonymous quadrantanopia. Discussion : The left superior homonymous quadrantanopia is caused by an infarction in the inferior calcarine of the occipital lobe due to the occlusion of a branch of the posterior cerebral artery. Atherosclerotic factors, such as hypertension, dyslipidemia, and hyperglycemia, are identified as the main causes of this condition. Normal pupillary responses and optic nerve appearance distinguish visual impairment caused by anterior lesions of the lateral geniculate body. Larger infarcts of the occipital lobe may result in neurological symptoms such as migraine with aura and visual hallucinations. Conclusion : The clinical manifestation of homonymous quadrantanopia should emphasizes the importance of ophthalmologic examinations, laboratory tests, perimetry, and imaging to estimate the location and etiology of the lesion.